2007
DOI: 10.5194/acp-7-1575-2007
|View full text |Cite
|
Sign up to set email alerts
|

Improved ozone profile retrievals from GOME data with degradation correction in reflectance

Abstract: Abstract. We present a simple method to perform degradation correction to Global Ozone Monitoring Experiment (GOME) reflectance spectra by comparing the average reflectance for 60 • N-60 • S with that at the beginning of GOME observations (July-December 1995) after removing the dependences on solar zenith angle and seasonal variation. The results indicate positive biases of up to ∼15-25% in the wavelength range 289-370 nm during 2000-2002; the degradation also exhibits significant dependence on wavelength and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…The first product is based on an optimal estimation technique by Liu et al (2007Liu et al ( , 2010 with modifications as described in Kim et al (2013), and is referred to as OMI/LIU hereafter. For OMI/LIU, errors for individual TCO retrievals are typically 2-5 DU (Liu et al, 2010).…”
Section: Two Omi Products For Tropospheric Column Ozonementioning
confidence: 99%
“…The first product is based on an optimal estimation technique by Liu et al (2007Liu et al ( , 2010 with modifications as described in Kim et al (2013), and is referred to as OMI/LIU hereafter. For OMI/LIU, errors for individual TCO retrievals are typically 2-5 DU (Liu et al, 2010).…”
Section: Two Omi Products For Tropospheric Column Ozonementioning
confidence: 99%
“…Furthermore, degradation of satellite instruments in the UV is often observed (e.g., GOME, Snel , 2000;Tanzi et al, 2000;van der A et al, 2002, andSCIAMACHY, Noël et al, 2007;Bramstedt et al, 2009). Several methods have been published to correct measured reflectances with modeled reflectances (e.g., van der A et al, 2002;Krijger et al, 2005;van Soest et al, 2005) or by comparing measured reflectances to those at the beginning of the mission after removing both solar zenith angle and seasonal dependencies (Liu et al, 2007;Tilstra et al, 2012a). Cai et al (2012) provide an extensive analysis of both the spectral and the cross-track degradation of GOME-2 measurements with time compared with model simulations and derived an empirical radiometric correction.…”
mentioning
confidence: 99%
“…3.1) this assumption can be regarded fulfilled but the earthshine radiance and, thus, the reflectance on the other hand depend strongly on highly variable atmospheric conditions such as clouds, trace gases, aerosols, or surface albedo and on the viewing angle. Therefore, retrievals using this correction may be inadequate for trend 20 studies (Liu et al, 2007). On the other hand, Garane et al (2018) have shown that using the latest version of the direct fitting approach GODFIT for ozone retrieval (GODFIT version 4) GOME (as well as OMI) performs in an extremely stable way and does not require any spectral soft calibration procedure.…”
mentioning
confidence: 99%
“…to degradation in the reflectance, which may affect for example ozone profile retrievals (van der A et al, 2002;Liu et al, 2007) or the determination of total ozone columns using a direct fitting approach (Lerot et al, 2014), because these algorithms are sensitive to absolutely calibrated reflectances. Correction approaches for the reflectance degradation have been developed in the past which rely on, e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation